The good fight : a novel - Steel, Danielle; Miller, Dan John (Prince Frederick, Md. : Recorded Books, 2018)
The daughter and granddaughter of prominent Manhattan lawyers, Meredith McKenzie is destined for the best of everything: top schools, elite social circles, the perfect marriage. Spending her childhood in Germany as her father prosecutes Nazi war criminals at the Nuremberg trials, Meredith soaks up the conflict between good and evil as it plays out in real time. When her family returns to the United States, she begins blazing her own trail, swimming against the tides, spurred on by her freethinking liberal grandfather, determined to become a lawyer despite her traditional, conservative father's objections. She forges a lifelong friendship with a young German Jewish woman whose family died in the concentration camps. And while her grandfather rises to the Supreme Court, Meredith enlists in the most pressing causes of her time, fighting for civil rights and an end to the Vietnam War. From the bright morning of JFK's inauguration, through the tumultuous years that follow as America hurtles toward the twin assassinations of Martin Luther King and Bobby Kennedy, Meredith joins the vanguard of a new generation of women, breaking boundaries socially, politically, and professionally. But when the violence of the era strikes too close to home, her once tightly knit family must survive a devastating loss, and rethink their own values and traditions in light of the times.
Subtitle from book and container.
Unabridged.
Narrated by Dan John Miller.
Compact disc.
Keywords: Families -- Fiction; Nineteen sixties -- Fiction; United States -- History -- 20th century -- Fiction; Audiobooks